Animal models on HTLV-1 and related viruses: what did we learn? - El Hajj, Hiba A.; Nasr, Rihab; Kfoury, Youmna; Dassouki, Zeina; Nasser, Roudaina; Kchour, Ghada; De Thé, Hugues; Hermine, Olivier; Bazarbachi, Ali (Frontiers in Microbiology, 2012)
Oncoviridae regroup several related retroviruses such as Human T-cell lymphotropic viruses (HTLV), Simian T cell lymphotropic viruses (STLV), and Bovine leukemia virus (BLV). Here we present an overview on different animal models used in the study of these viruses. These models vary from naturally infected animals to established, engineered or xenograft models. A special attention will be given to the HTLV-1 virus, the causative agent of adult T-cell leukemia/lymphoma (ATL) and a number of inflammatory diseases such as the HTLV-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Monkeys, rabbits and rats provide an excellent in vivo tool for the study of early viral infection and transmission as well as the antiviral host immune response. However, because of their small size and the availability of reagents, mice remain the most efficient method of studying human afflictions. Murine models regroup genetically altered mice including both transgenic and knock-out mice, as well as immunodeficient mice strains. The first group offers important models to test the role of specific viral and host genes in the development of HTLV-I associated leukemia whereas the second group provides a useful and rapid tool of humanized and xenografted mice models. These later are widely used to test new drugs and targeted therapy against HTLV-1 associated leukemia, to identify potential leukemia stem cells, and to study the innate immunity against the virus. Altogether, these animal models have revolutionized the biology of retroviruses, their manipulation of host genes and more importantly the potential ways to either prevent their infection or to treat their associated diseases.